Microwave-assisted synthesis, characterization and cytotoxic studies of novel estrogen receptor α ligands towards human breast cancer cells. Issue 8 (15th April 2015) - Bharathkumar, Hanumantharayappa; Mohan, Chakrabhavi Dhananjaya; Ananda, Hanumappa; Fuchs, Julian E.; Li, Feng; Rangappa, Shobith; Surender, Mohan; Bulusu, Krishna C.; Girish, Kesturu S.; Sethi, Gautam; Bender, Andreas; Basappa; et al.
Graphical abstract